2016
DOI: 10.1073/pnas.1603712113
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic profiling reveals an association between persistence of DNA methylation and metabolic memory in the DCCT/EDIC type 1 diabetes cohort

Abstract: We examined whether persistence of epigenetic DNA methylation (DNA-me) alterations at specific loci over two different time points in people with diabetes are associated with metabolic memory, the prolonged beneficial effects of intensive vs. conventional therapy during the Diabetes Control and Complications Trial (DCCT) on the progression of microvascular outcomes in the long-term followup Epidemiology of Diabetes Interventions and Complications (EDIC) Study. We compared DNA-me profiles in genomic DNA of whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
185
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(203 citation statements)
references
References 68 publications
12
185
0
1
Order By: Relevance
“…60,65,66 Even if hyperglycemia is short lasting, changes in the epigenome could persist due to metabolic memory. 67,68 Three genome-wide methylation studies revealed DR-specific DNA methylation profiles, and identified the natural killer cellmediated cytotoxicity pathway as potentially involved in DR pathogenesis. [67][68][69] Interestingly, an increase in global DNA methylation levels in blood has been correlated to the severity of DR, independent of common DR risk factors.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
See 1 more Smart Citation
“…60,65,66 Even if hyperglycemia is short lasting, changes in the epigenome could persist due to metabolic memory. 67,68 Three genome-wide methylation studies revealed DR-specific DNA methylation profiles, and identified the natural killer cellmediated cytotoxicity pathway as potentially involved in DR pathogenesis. [67][68][69] Interestingly, an increase in global DNA methylation levels in blood has been correlated to the severity of DR, independent of common DR risk factors.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…67,68 Three genome-wide methylation studies revealed DR-specific DNA methylation profiles, and identified the natural killer cellmediated cytotoxicity pathway as potentially involved in DR pathogenesis. [67][68][69] Interestingly, an increase in global DNA methylation levels in blood has been correlated to the severity of DR, independent of common DR risk factors. 67 This suggests DNA methylation patterns as potent candidate biomarkers for DR, although these findings warrant replication in larger cohorts.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…45,46 Of interest, a recent study demonstrated that specific microRNA (i.e., miR-125b and miR-146a-5) changes can cause persistent increase in proatherogenic gene expression and explain in this way the phenomenon of metabolic memory. 47 The key role of glycemic control in modulating complication risks highlighted by the DCCT/EDIC studies was also confirmed by large studies performed in adults with T2D, such as the UKPDS, where for example intensive treatment (insulin or sulfonylurea) resulted in a 25% decrease in microvascular complications.…”
Section: -42mentioning
confidence: 99%
“…This hypothesis is supported by the recently published results of the study by Chen et al [33], in which the level of methylation of selected loci throughout the genome was evaluated among the participants of the EDIC study with an interval of more than 16 years. It was shown that the DNA methylation profile of study participants who were subjected to conventional therapy and who developed retinopathy or microalbuminuria differs from the DNA methylation profile of participants with intensive glycemic control.…”
Section: Epigenetic Modifications and The Course Of Type 2 Diabetesmentioning
confidence: 53%
“…It was shown that the DNA methylation profile of study participants who were subjected to conventional therapy and who developed retinopathy or microalbuminuria differs from the DNA methylation profile of participants with intensive glycemic control. Only in the conventionally treated group, in which adequate glycemic control was not achieved, persistent hypomethylation of the gene for thioredoxin-responsive protein (TXNIP) was found, the consequence of which may be increased expression of this protein [33].…”
Section: Epigenetic Modifications and The Course Of Type 2 Diabetesmentioning
confidence: 99%